Timing of intermittent seminal HIV-1 RNA shedding in patients with undetectable plasma viral load under combination antiretroviral therapy. - Xavier Ferraretto; Candice Estellat; Florence Damond; Pascale Longuet; Sylvie Epelboin; Pauline Demailly; Chadi Yazbeck; Marie-Astrid Llabador; Blandine Pasquet; Yazdan Yazdanpanah; Sophie Matheron; Catherine Patrat (PLoS ONE)
It was demonstrated that combination antiretroviral therapy (cART) reduces the HIV-1 viral load (VL) in the blood and the seminal compartment. Some studies have reported that the seminal HIV-1 VL is undetectable in individuals with an undetectable blood plasma viral load (bpVL) under cART. However, some recent studies have demonstrated that seminal HIV-1 RNA may still be detected, and potentially infectious, even in the case of an undetectable bpVL. The aim of this retrospective study was to determine the detection rate of a seminal VL and whether shedding could be intermittent over a very short time. From January 2006 to December 2011, 88 HIV-1 infected men, enrolled in an Assisted Reproduction program, provided 306 semen samples, corresponding to 177 frozen sperm samples (two samples delivered at a one-hour interval (n = 129) or one sample (n = 48)). All enrolled men were under cART, with an undetectable bpVL for more than 6 months. HIV-1 RNA was quantified in seminal plasma using a Roche COBAS Ampliprep COBAS TaqMan HIV-1 test. Seminal HIV-1 RNA was detected in 23 samples (7.5%) from 17 patients (19.3%). This detection rate was stable over years. With regards to the freezing of two samples delivered at a one-hour interval, the proportion of discordance between the first and second samples was 9.3% (12/129). Our results confirm the intermittent shedding of HIV-1 in semen. While this finding has been shown by studies examining longer time intervals, to our knowledge, this has never been demonstrated over such a short time interval.